Television's Transition to the Internet: Disability Accessibility and Broadband-Based TV in Australia. Issue 1 (November 2014) - Ellis, Katie
Whereas entertainment has featured negatively in the broader NBN debate currently occurring in Australia, within the disability sector it has been recognised as revolutionary. Government, industry and technical analysts describe digital television, particularly that delivered via broadband, as potentially enabling to people with vision and hearing impairments through the more widespread provision of accessibility features such as audio description and closed captions. This article interrogates the approach to accessibility taken by two case studies of broadband-based television: Netflix and catch-up TV. Netflix, which is not officially available in Australia, is often presented as the future of television, while catch-up services provide an example of the current broadband-based television paradigm in this country. Although accessibility features may be available on broadcast television or DVD release, each of these forms of broadband-based television has either previously (Netflix) or currently (catch-up) stripped accessible functions to stream online. The discussion reflects on both activist interventions of people with disability and the industry standards.